2014
DOI: 10.1080/10810730.2014.934933
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Health Literacy with Physical Activity and Nutritional Behavior in Older Adults, and Its Social Cognitive Mediators

Abstract: Inadequate health literacy is a common problem among older adults and is associated with poor health outcomes. Insight into the association between health literacy and health behaviors may support interventions to mitigate the effects of inadequate health literacy. The authors assessed the association of health literacy with physical activity and nutritional behavior in community-dwelling older adults. The authors also assessed whether the associations between health literacy and health behaviors are mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
74
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 46 publications
8
74
1
8
Order By: Relevance
“…Some literatures showed that social participation was related to better health-related quality of life [22], functional skills [23], and even survival [24]. Inadequate health literacy was a common problem among older adults and was associated with poor health outcomes [25]. Meanwhile, The elderly can communicate with others in activities, which is a good way for them to improve their behaviors through mutual exchanges and learning to improve their health.…”
Section: Discussionmentioning
confidence: 99%
“…Some literatures showed that social participation was related to better health-related quality of life [22], functional skills [23], and even survival [24]. Inadequate health literacy was a common problem among older adults and was associated with poor health outcomes [25]. Meanwhile, The elderly can communicate with others in activities, which is a good way for them to improve their behaviors through mutual exchanges and learning to improve their health.…”
Section: Discussionmentioning
confidence: 99%
“…First, future analyses will consider the role of post-intervention change in self-efficacy in the relationship between health literacy and FIT kit update as prior studies have suggested that self-efficacy may mediate the relationship between health literacy and health behaviors or health outcomes (Geboers, de Winter, Luten, Jansen, & Reijneveld, 2014; Jones, Brennan, Parker, Mills, & Jamieson, 2016; Kim & Yu, 2010). Indeed, one previous study suggested that health literacy mediated the relationship between educational achievement and prior CRC screening behavior among medically-underserved individuals (Ojinnaka et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a previous study showing a positive relation between physical activity and health literacy in older adults. 26 Health literacy has also been shown to predict self-efficacy for physical activity among sedentary Latinas. 27 …”
Section: Discussionmentioning
confidence: 99%